Depression in Multiple Sclerosis: Lifestyle Interventions as an Additional Therapeutical Approach: A Narrative Review - Matea Hudolin; Hrvoje Budinčević; Dunja Degmečić; Vida Demarin (Psychiatry International)
Depression is one of the most common comorbidities in people with multiple sclerosis, which reduces the quality of life and treatment adherence. It enhances the risk of disease relapse. After looking through the literature, we summarized the newest recommendations that might be helpful in reducing depression severity by reviewing publications regarding depression and multiple sclerosis published in the last five years. Physical activity and rehabilitation should be recommended. The ketogenic diet showed promising results, yet there are possible health concerns that might evolve after a longer period and should only be carried out under medical supervision. Mindfulness and cognitive and dialectical behavior therapy reduce depression severity and can be recommended to depressive people with multiple sclerosis.